Work-related participation impairments and support needs of patients in a Swiss psychiatric university hospital - Hug, Niki; Imfeld, Lukas; Holinger, Benjamin; Jäckel, Dorothea; Huber, Christian G.; Nienaber, André (Frontiers in Psychiatry, 2024)
Objective To assess work-related participation impairments and support needs of adult patients in inpatient and day-care treatment at a Swiss psychiatric university hospital Methodology Cross-sectional survey on a department-dependent cut-off date in May and June 2022 using a standardised structured interview. Results Data were available for 93 patients (response rate 59%), of which 51% (n=47) stated that they had a job or training place. Patients in first hospitalisation and with a job or training place were approached significantly more often. Regardless of age and first hospitalisation, 76% of the patients expressed a need for support, of which 92% expressed interest in job coaching. A total of 54% of the patients stated that they had received support from the treatment team. Conclusion From the patients’ point of view, work and education were not addressed by the treatment team across the board and independently of patient characteristics. The need for support was insufficiently met. There is a considerable interest for support programmes through job coaching, and this offers opportunities to promote the inclusion of patients in the regular labour market.